VN–VIn divacancies as the origin of non-radiative recombination centers in InGaN quantum wells - Anna Toschi; Yao Chen; Jean-François Carlin; Raphaël Butté; Nicolas Grandjean (APL Materials)
In this paper, we investigate the nature of surface defects originating from the high-temperature (HT) GaN buffer and their incorporation into InGaN quantum wells (QWs) grown using the metalorganic vapor phase epitaxy technique. In particular, we conduct a detailed examination of the migration process of these defects from the HT-GaN buffer to the QWs, focusing on two potential pathways: diffusion versus surface segregation. A careful study confirms surface segregation as the dominant migration mechanism. To further understand the defect nature, we evaluate the stability of the HT-GaN surface under different annealing conditions, including different combinations of temperature and ammonia flow. We find that higher annealing temperatures or reduced ammonia flows significantly enhance the formation of defects, which speaks in favor of nitrogen vacancies (VN). Finally, we propose that these VN vacancies segregate toward the surface and interact with indium vacancies (VIn) in InGaN layers, forming VN–VIn divacancies. These VN–VIn divacancies could be the primary defects incorporated into InGaN layers acting as the main non-radiative recombination centers in InGaN QWs.